Correlation of Anemia Status in Mothers and Stunted Toddlers - Florida Ester Pailau; Michael Bhadi Bia; Supriati Wila Djami; Ni Ketut Yuliana Sari; Atun Farihatun (Poltekkes Kemenkes Kupang, 2025)
Postpartum anemia remains a public health concern due to its potential impact on maternal and child health. This study aimed to analyze the correlation between maternal anemia status and anemia among stunted toddlers. An analytical observational study with a cross-sectional design was conducted at Pustu Noelbaki. The study subjects were mothers and their stunted toddlers selected using purposive sampling. A total of 40 participants were included, consisting of 20 mothers and 20 stunted toddlers. Maternal and toddler anemia status were assessed and analyzed using statistical correlation testing with a significance level of p < 0,05. The results showed that 25% of mothers were anemic, while 55% of stunted toddlers had anemia. Statistical analysis demonstrated a p-value of 0,319 (p > 0,05), indicating no significant correlation between maternal anemia status and anemia among stunted toddlers. In conclusion, maternal anemia was not significantly associated with anemia in stunted toddlers in this study. Further research with larger sample sizes is recommended to better understand potential contributing factors.